Study of the Properties of TiO2 Doped with Nitrogen and Magnesium using DR-UV Vis Analysis as Catalyst in Wastewater Treatment - Razali, Nur ‘Aliaa; Othman, Siti Amira (IOP Publishing, 2020)
Due to the environmental issue that have become serious each day, many researchers interested to solve the problem with few method of water treatment including carbon adsorption, ultrafiltration, coagulation using chemical method, biodegradation using microbes, ozonation and also advanced oxidation process. One of the popular methods is using doping method. The photocatalytic activity is said to be directly proportional to the dopant concentration based on previously study. The optimum photocatalytic activity will occur at optimum dopant concentration, but at certain level of dopant concentration, the photocatalytic efficiency will be decreasing. DR-UV Vis analysis shows that the nitrogen and magnesium doped caused the formation of new mid-gap energy state and make the band gap shifted.